The politics and possibilities of self-tracking technology : data, bodies and design - Jethani, Suneel (Emerald Publishing Limited, 2021)
Collecting data about our lives, our bodies and our behaviours has become a part of everyday practice that promises greater self-awareness, healthier living and increased productivity. This book focuses on the dialectical relationship between users and designers of self-tracking technology to examine how logics of datafication redefine the body. It explores what these emerging relations mean for imagining, designing and analysing sociotechnical systems that bring about self-tracking. Jethani provides a genealogy of self-tracking to situate the notions of quantified and quantifiable selves as problematic data regimes within contemporary digital culture. It charts the origins of self-tracking from within the blueprint of the "Californian Ideology" to a global social movement which now reaches beyond self-experimentation to encompass the wider trajectories of using wearable sensor technology in the neoliberal management of health, wellbeing and productivity. The book reframes and theorises the quantified self by re-examining and developing arguments of how bodies "disappear" (Jewson), are made "docile" (Foucault) and get caught up in "rhythms" (Lefebvre) by datafication. The concept of a "quantised" self is introduced as a means of reading into and exposing the inherent political interests being served when self-tracking technology is introduced into clinical, home and workplace settings. Drawing from case studies of self-tracking in practice, the final chapter sketches the outline of a mutual praxis of critique and design that allows us to reimagine the politics embedded in sociotechnical systems of self-tracking and to consider possibilities of intervention.